2020
DOI: 10.1002/1873-3468.13742
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient gene silencing in mouse brain by overhanging‐duplex oligonucleotides via intraventricular route

Abstract: Gapmer‐type antisense oligonucleotides have not yet been approved for the treatment of central nervous system diseases, whereas steric‐blocking‐type antisense oligonucleotides have been well‐developed for clinical use. We here characterize a new type of double‐stranded oligonucleotides, overhanging‐duplex oligonucleotides, which are composed of the parent gapmer and its extended complementary RNA. By intracerebroventricular injection, overhanging oligonucleotides show greater silencing potency with more effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…injection into mice. 32 However, we have not yet reported that ASO3 has moderate neurotoxicity at the acute phase. We chose these three ASOs because we elucidate the general mechanisms underlying acute neurotoxicity via the intrathecal (IT) route using these ASOs with different lengths and chemical modifications.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…injection into mice. 32 However, we have not yet reported that ASO3 has moderate neurotoxicity at the acute phase. We chose these three ASOs because we elucidate the general mechanisms underlying acute neurotoxicity via the intrathecal (IT) route using these ASOs with different lengths and chemical modifications.…”
Section: Methodsmentioning
confidence: 95%
“…The chosen three toxic oligonucleotides with a PS backbone were two DNA/LNA gapmer-type ASOs 32 targeting mouse beta-site amyloid precursor protein cleaving enzyme ( Bace1 ) and microtubule-associated protein tau ( Mapt ) mRNAs, respectively, and one 20mer DNA/MOE gapmer-type ASO 33 targeting metastasis-associated lung adenocarcinoma transcript 1 ( Malat1 ) long non-coding RNA (as shown in Table S1 ). ASO1 was reported by Hagedorn et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 ). Binding of the leash sequence to the DNAzyme resulted in the formation of a duplex (made up of double-stranded DNA or RNA) and allowed the “escort” of the DNAzyme to target tissues [ 84 , 92–94 ]. In addition, DNAzyme stability is increased owing to the DNA/RNA or DNA/DNA duplex region being inherently more stable than single-stranded (ssDNA) DNA (DNAzyme) in the cellular environment.…”
Section: Noncarrier Molecule Modificationsmentioning
confidence: 99%
“…Up to date, three gapmers have been approved for clinical use, Mipomersen, Inotersen, and Volanesorsen. In addition to the single stranded oligonucleotides, double stranded DNA-RNA heteroduplex oligonucleotides (HDO) [ 30 , 31 ], and overhanging heteroduplex oligonucleotides (ODO) [ 32 ] were recently reported to have more potent gene silencing activities.…”
Section: Rna-based Therapymentioning
confidence: 99%